Integration of machine learning with complex industrial mining systems for reduced energy consumption - Harmse, Michael David; van Laar, Jean Herman; Pelser, Wiehan Adriaan; Schutte, Cornelius Stephanus Lodewyk (Frontiers in Artificial Intelligence, 2022)
The deep-level mining industry is experiencing narrowing profit margins due to increasing operating costs and decreasing production. The industry is known for its lack of dynamic control across complex integrated systems running deep underground, making IoT technologies difficult to implement. An important integrated system in a typical underground mine is the refrigeration-ventilation system. In practice, the two systems are still controlled independently, often due to a lack of continuous measurements. However, their integrated effects ultimately affect energy usage and production. This study develops and compares various machine learning prediction techniques to predict the integrated behaviour of a key component operating on the boundary of the refrigeration-ventilation system, while also addressing the lack of continuous measurements. The component lacks sensors and the developed industrial machine learning models negate the effect thereof using integrated control. The predictive models are compared based on accuracy, prediction time, as well as the amount of data required to obtain the required level of accuracy. The 'Support Vector Machines' method achieved the lowest average error (1.97%), but the 'Artificial Neural Network' method is more robust (with a maximum percentage error of 12.90%). A potential energy saving of 215 kW or 2.9% of the ventilation and refrigeration system, equivalent to R1.33-million per annum ($82 900) is achievable using the 'Support Vector Machines' method.